Luis Jerónimo de Oré OFM — Symbolo Catholico Indiano (1598) - Kaproń OFM, Kasper (Poznańskie Studia Teologiczne, 2020)
Brother Luis Jerónimo de Oré’s Symbolo Catholico Indiano was the most important and authorized sixteenth century treatise for the evangelization of the native Andean peoples. In its pages we find a vivid image of Andean reality immediately after the Conquest and a fervent exposition of the Catholic faith inspired in the recent Councils of Trent and Lima. The treatise also presents the missioning methods that served the Franciscans and other priests of the Viceroyalty for the evangelization of the indigenous peoples. Above all, in this text we find an admirable exposition of the theological doctrine and catechetical practice in the anthropological perspective that forms its starting point, which is the Andean man or woman who had never heard a message of salvation and dignity for the human person. Brother Luis Jerónimo de Oré Rojas OFM was born in Huamanga in 1554 (now the geographi- cal Department of Ayacucho in Perú). He was a zealous missionary who travelled throughout the colonizers’ territory, from the extreme north of Florida to the extreme south of Chile. As an intelli- gent linguist he was the author of important rituals and catechisms in Quechua and Aymara. He was one of the first bishops born on the American soil, and the first to be incorporated into the Native Indian Council and the Vatican hierarchy; as a bishop he stood out for his protection of aboriginal groups and his energetic defense of the cultural integrity of Native Indian nations.